SELF-ACTUALIZATION IN JANE EYRE’S MAIN CHARACTER : A FEMINISM STUDY - LIN JIN; Yohanes Kurniawan Winardi; Endar Rachmawaty Linuwih (ELite Journal : International Journal of Education, Language, and Literature, 2022)
This study focuses on Charles Fourier's feminism and Maslow's self-actualization. The writers concentrate on Maslow's self-actualization theory's self-esteem prerequisite and five personality traits in this study. This study is qualitative research, and it employs descriptive-analytic methods. This study examines Jane Eyre's utterances and actions to uncover her personality traits in the novel Jane Eyre, to analyze Jane Eyre's inner feminist thinking. It is worth emphasizing that this research uses feminism as the theoretical background to explain the personality characteristics of Jane Eyre's inherent self-actualization. A conclusion was reached at the end of the discussion. Jane Eyre satisfies the need for self-esteem, has a self-esteem personality, and expresses the five self-actualization personality traits. Five of them are perceiving reality, accepting the self and others, being problem-centrist, independent, resisting, and criticizing the existing social culture. This research serves as a reference for studying feminist thought and is limited to looking at its thoughts through inner personality traits, suitable for providing references for people who want to know how to achieve self-actualization in society.